Sebetralstat: A Rapidly Acting Oral Plasma Kallikrein Inhibitor for the On-Demand Treatment of Hereditary Angioedema - Edward P. Feener; Rebecca L. Davie; Nivetha Murugesan; Stephen J. Pethen; Sally L. Hampton; Michael D. Smith; Paul K. Audhya; Chris M. Yea (MDPI AG, 2024)
Sebetralstat is a novel, potent, and selective oral plasma kallikrein inhibitor drug candidate in clinical development for the on-demand treatment of hereditary angioedema (HAE). Upon binding, sebetralstat induces a conformational change in the active site of plasma kallikrein, which contributes to its high potency (Ki 3 nM) and selectivity (>1500 fold) against other serine proteases. Its physiochemical properties promote both rapid dissolution in the stomach and rapid absorption in the upper intestine that contribute to its fast and efficient absorption. A single oral administration of sebetralstat rapidly provides near-complete inhibition of plasma kallikrein and blockade of high-molecular-weight kininogen cleavage as early as 15 min, which drives its clinical efficacy. In a phase 2 clinical trial, sebetralstat significantly reduced the time to beginning of symptom relief (p < 0.0001) with median times of 1.6 h (95% CI: 1.5-3.0) with sebetralstat versus 9.0 h (4.0-17.2) with placebo. KONFIDENT (NCT05259917) is a phase 3 clinical trial assessing the on-demand use of sebetralstat for HAE. If successful, this trial could support the approval of sebetralstat as the first noninvasive, on-demand treatment option to rapidly halt HAE attacks and provide fast symptom relief.